Indium-catalyzed formal (4 + 1 + 1)/(4 + 1) isocyanide-based annulation for construction of polyfunctionalized pyrano- and furoquinolines - Zarei, Issa; Khosravi, Hormoz; Rominger, Frank; Somee, Leila Rezaei; Balalaie, Saeed (Organic & biomolecular chemistry, 2025)
A distinctive catalytic reaction involving multiple isocyanide insertions on ambiphilic quinolines has been introduced to synthesize intricate polyheterocyclic scaffolds (21 examples, up to 71% yield) through the formation of several C-C, C-O, and C-N bonds. Our findings indicate that these reactions can switch between two cycloadditions ([4 + 1 + 1] and [4 + 1]) depending on the isocyanide structure and the solvent used. Finally, furo[2,3-b]quinoline-2,3-diamine examples, as some of the novel products, exhibit strong solvatochromism in various solvents.